Pengaruh Promosi Dan Pelayanan Terhadap Kepuasan Pelanggan Pasca Bayar Pada Grapari Telkomsel Mini Multatuli - M Ridwan; Selamat Pohan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
Service quality is a form of service assessment of the level of service received (perceived service) with the level expected (expected to be served). In order to compete, survive, and develop, the company is able to meet the needs and desires of consumers by providing the best and quality service, the problem found is the lack of a service activity in maintaining customer satisfaction at grapari telkomsel mini multatuli.promosi is a marketing effort that provides short-term intense efforts to induce the desire to try or buy a product or service. service level is a form of consumer assessment of the service received with the level of service that is expected to be able to compete. This study discusses the effect of promotion and service on customer satisfaction. Using quantitative methods with the number of respondents 122 people (customers). this study is that there is an effect of promotion on customer satisfaction with an effect (X1) on customer satisfaction (Y), because the value of ttable > tcount (4,868 > 1,677). Service has a significant and significant effect on customer satisfaction with the value of Fcount > Ftable obtained 43,389 > 3.191. Together or simultaneously promotion and service affect customer satisfaction.